Pengaruh program brisk walking exercise terhadap penurunan tekanan darah pada penderita hipertensi - Septi Andrianti; Ikhsan Ikhsan (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2021)
The effect of brisk walking exercise program on blood pressure for people with hypertension Background: Some patients with hypertensive only use antihypertensive drugs to decrease their blood pressure. There are alternatives and more effective as non-pharmacological alternatives to help decrease blood pressure.Purpose: To determine the effect of brisk walking exercise program on blood pressure for people with hypertensionMethod: Quasi-experimental design, the participants were divided into two groups (intervention group and nonintervention group). The sample of this study was 20 participants with contraindications taken by consecutive Sampling. Brisk walking exercise program for 20-30 minutes with an average speed of 4-6km/hour. Three times a week for two months. Data analyzed using a dependent t-test with a 95% confidence level.Results: The study showed that the mean of the intervention systolic pressure before intervention (154.00±10.75) with range (140-170) and after intervention (140.00±8.17) with range (130-160)(p-value=0.001). In the control group, mean the systolic pressure (143.00±8.23) with range (130-150) and after two months (135.50±5.50) with range (130-150). The mean of the diastolic pressure (Intervention group) before (97.00±6.75)with range (90-110) and after (85.00±4.71) with range (80-90). The control group (93.00±6.32) (80-100) and after (89.00±5.16) with range (85-95)(p-value=0.001)Conclusion: There was a significant effect of the brisk walking exercise program in the intervention group, which was stronger than the control group.Keywords: Brisk walking exercise; Blood pressure; Hypertension Pendahuluan: Beberapa penderita hipertensi hanya menggunakan obat antihipertensi untuk menurunkan tekanan darahnya. Ada alternatif dan lebih efektif sebagai alternatif non-farmakologis untuk membantu menurunkan tekanan darah.Tujuan: Untuk mengetahui pengaruh program brisk walking exercise terhadap penurunan tekanan darah pada penderita hipertensi.Metode: Quasi-experimental design, peserta dibagi menjadi dua kelompok (kelompok intervensi dan kelompok Kontrol). Sampel penelitiannya 20 partisipan tanpa kontraindikasi yang diambil secara Consecutive Sampling. Program brisk walking exercise selama 20-30 menit dengan kecepatan rata-rata 4-6km/jam. Tiga kali seminggu selama dua bulan. Data dianalisis menggunakan uji-t dependen dengan tingkat kepercayaan 95%.Hasil: Menunjukkan bahwa rerata tekanan sistolik intervensi sebelum intervensi (154,00±10,75) dengan rentang (140-170) dan setelah intervensi (140,00±8,17) dengan rentang (130-160)(p-value=0,001). Pada kelompok kontrol, rata-rata tekanan sistolik (143,00±8,23) dengan kisaran (130-150) dan setelah dua bulan (135,50±5,50) dengan rentang (130-150). Rerata tekanan diastolik (kelompok intervensi) sebelum (97,00±6.75) dengan rentang (90-110) dan setelahnya (85,00±4,71) dengan rentang (80-90). Kelompok kontrol (93.00±6.32) dengan rentang (80-100) dan setelahnya (89,00±5,16) dengan rentang (85-95)(nilai-p=0,001)Simpulan: Ada pengaruh yang signifikan dari program brisk walking exercise pada kelompok intervensi yang lebih kuat dibandingkan kelompok kontrol.